Kontribusi Kekuatan Otot Lengan Dan Kekuatan Otot Tungkai Terhadap Kecepatan Renang Gaya Bebas 50 Meter - Yogi Setiawan; Naluri Denay (Universitas Negeri Padang, 2022)
Based on observations, the problem in this study is the lack of 50 meter swimming front crawl athletes in Padang. So this study aims to determine the contribution of the strength of the arm, leg muscles to the speed of 50 swimming front crawl. This research is a type of correlation with a sample of 11 athletes consisting of 6 boys and 5 girls. Sampling was done by purposive sampling. The instruments used are push ups, leg dynamometers and use a 50 meter swimming front crawl speed test in seconds. The data analysis technique used is a simple Pearson product moment multiple correlation analysis. The results showed that there was a contribution between arm muscle strength and swimming speed for male athletes by 77.9%, female athletes by 98.8%. Leg muscle strength to swimming speed for male athletes is 55.9%, female athletes are 97%. Then, the arm muscle strength and leg muscle strength together to the 50 meter swimming front crawl speed in male athletes are 72.3%, female athletes are 90.3%.